Future-Proofing Potato for Drought and Heat Tolerance by Overexpression of Hexokinase and SP6A - Lehretz, Günter G.; Sonnewald, Sophia; Lugassi, Nitsan; Granot, David; Sonnewald, Uwe (Frontiers in Plant Science, 2021)
Crop yield is largely affected by global climate change. Especially periods of heat and drought limit crop productivity worldwide. According to current models of future climate scenarios, heatwaves and periods of drought are likely to increase. Potato, as an important food crop of temperate latitudes, is very sensitive to heat and drought which impact tuber yield and quality. To improve abiotic stress resilience of potato plants, we aimed at co-expressing hexokinase 1 from Arabidopsis thaliana (AtHXK1) in guard cells and SELF-PRUNING 6A (SP6A) using the leaf/stem-specific StLS1 promoter in order to increase water use efficiency as well as tuberization under drought and heat stress. Guard cell-specific expression of AtHXK1 decreased stomatal conductance and improved water use efficiency of transgenic potato plants as has been shown for other crop plants. Additionally, co-expression with the FT-homolog SP6A stimulated tuberization and improved assimilate allocation to developing tubers under control as well as under single and combined drought and heat stress conditions. Thus, co-expression of both proteins provides a novel strategy to improve abiotic stress tolerance of potato plants.